Reflection of Stress in the Oral Cavity (Indian Journal of Forensic Medicine & Toxicology, 2020)
Stress is based on the physical, mental, or emotional reaction to events which cause tension in the body ormind. Different types of diseases affect the human body, some of which may have an unknown etiology. Itis one such etiology that predisposes many diseases. Dentists often come across patients in their everydaypractice showing signs of stress and about their oral manifestations in the form of recurrent aphthous ulcer,oral lichen planus, and temporomandibular disorders, xerostomia, burning mouth syndrome, bruxism,periodontal disease, dental caries. Identification of such an emotional or psychological disorder stands tobenefit both the patient and the practitioner. Consequently, psychological management should be consideredwhen treating patients with any of these psychosomatic disorders. This review literature discussed commonoral manifestation of stress.